Plasmon Catalysis on Bimetallic Surface—Selective Hydrogenation of Alkynes to Alkanes or Alkenes; Journal of Physical Chemistry C; Vol. 122, iss. 46 - Guselnikova O. A. Olga Andreevna; Olshtrem A. A. Anastasiya Andreevna; Kalachyova E. Evgeniya; Postnikov P. S. Pavel Sergeevich; Svorcik V. Vaclav; Lyutakov O. Oleksy (2018, 2018)
Title screen